Intencionalidade e dolo: aspectos hermenêuticos, linguístico-pragmáticos e cognitivos por trás do debate dogmático - Thiago Dias de Matos Diniz (2018)
In the last years, despite the major adoption of psychological and volitional conceptions of intent (dolo) in Brazilian criminal law, the normative theses which question the presence of psychological facts or states on the definition of intent are growing with substantial theoretical background. Debate between the opposite sides, however, seems distorted by series of conceptual confusions, the origins of which remain on extra dogmatic level. This work shows some basic problems regarding the way by which arguments from both sides are constructed, mainly, hermeneutic, pragmatic and empirical-cognitive problems. The first are issued from a phenomenological reconstruction of both Welzels Finalismus and the question about the demonstrability of a consciousness mental state. The second ones are issued through the contributions of contemporary philosophy of language to the understanding of the way by which we employ psychological concepts as intention, and their relationship with the meaning, especially moral, of an action. The last field of problems is opened due to neuroscience findings on our intuitive responsibility and intentional attribution which affect the conformation of a case under intent (dolo) and reveal traces and factors up to now hidden behind the reductive rationalist model of consciousness and representation assumed by criminal law, on the authors side, and behind the guarantee of a judgement strictly grounded on facts, on the side of judicial cognition and argumentation. As those problems emerge, one may detect their relation to some unresolved questions in the dogmatics of intent (dolo) and analyze attempts to solve them with contemporary theories on the subjective element of fact species.